2018
DOI: 10.3390/app8101755
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Strain Monitoring of Railway Composite Bogies Using a Brillouin Optical Correlation Domain Analysis System

Abstract: The structural deformation of a bogie frame manufactured using a composite material was monitored in real time using a distributed optical fiber sensor. The bogie frame contained an internally embedded standard single-mode optical fiber. Performance tests were conducted by applying a vertical load to the middle of the side beams on each side of the composite bogie frame. The strain distribution was monitored using an optical fiber sensor. A distributed optical fiber sensor system based on the Brillouin optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Further investigations on the dynamic properties of the composite bogie frame showed that even by eliminating the primary suspension system in the composite frame, dynamic wheel unloading, wheel wear index, and ride comfort satisfy the design requirements 24,31 . More recently, distributed optical fiber sensors were employed to monitor the structural deformation of the developed composite bogie in real‐time 32 . The presented monitoring method, represents a viable way for a real time evaluation of the composite structure's health status.…”
Section: Applications Of Frps In Railway Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations on the dynamic properties of the composite bogie frame showed that even by eliminating the primary suspension system in the composite frame, dynamic wheel unloading, wheel wear index, and ride comfort satisfy the design requirements 24,31 . More recently, distributed optical fiber sensors were employed to monitor the structural deformation of the developed composite bogie in real‐time 32 . The presented monitoring method, represents a viable way for a real time evaluation of the composite structure's health status.…”
Section: Applications Of Frps In Railway Vehiclesmentioning
confidence: 99%
“…24,31 More recently, distributed optical fiber sensors were employed to monitor the structural deformation of the developed composite bogie in real-time. 32 The presented monitoring method, represents a viable way for a real time evaluation of the composite structure's health status. This system makes it possible to determine whether delamination or cracks in composites happen during running time of the bogie.…”
Section: Gfrp Sandwich Bogie Frame Frp Bogiementioning
confidence: 99%
“…The above mentioned BFS sensing method had been used in railway composite bogies [8] and railway bridge [9] measurement.…”
Section: Brillouin Frequency Shiftmentioning
confidence: 99%